Beneath the sands of egypt eaudiobook Adventures of an unconventional archaeologist. - Ryan, Donald P. (Tantor Media, 2020)
A real-life "Indiana Jones," Donald P. Ryan, PhD, offers a breathtaking personal account of his adventures in archaeology in Beneath the Sands of Egypt . Fans of The Lost City of Z will thrill to the exploits of this "unconventional archaeologist" as he retrieves the remains of Egypt's past—including his breakthrough discovery in the Valley of the Kings of Egypt's famous female pharaoh, Hatshepsut.